2021
DOI: 10.1242/dev.199216
|View full text |Cite
|
Sign up to set email alerts
|

Hypomorphic and hypermorphic mouse models of Fsip2 indicate its dosage-dependent roles in sperm tail and acrosome formation

Abstract: Loss-of-function mutations in multiple morphological abnormalities of the sperm flagella (MMAF)-associated genes lead to decreased sperm motility and impaired male fertility. As an MMAF gene, the function of fibrous sheath-interacting protein 2 (FSIP2) remains largely unknown. In this work, we identified a homozygous truncating mutation of FSIP2 in an infertile patient. Accordingly, we constructed a knock-in (KI) mouse model with this mutation. In parallel, we established an Fsip2 overexpression (OE) mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 48 publications
(83 reference statements)
1
8
0
Order By: Relevance
“…In patients harboring FSIP2 mutations, the defects in sperm are not limited to abnormalities in the FS but also cause abnormalities in the microtubule skeleton. A recent study has reported that FSIP2 mutant sperm show a globozoospermia phenotype in addition to flagella defects, and FSIP2 localizes in the acrosome and interacts with proteins associated with acrosome formation, indicating the potential function of FSIP2 in acrosome development (Zheng et al, 2022), which is consistent with single-cell RNA-seq data (Fang et al, 2021). FSIP2 has been demonstrated to interact with two other FS proteins, namely, AKAP3 and AKAP4, which are encoded by MMAF causative genes (Zhang G. et al, 2021;Liu Z. et al, 2022).…”
Section: Periaxonemal Structuressupporting
confidence: 84%
See 1 more Smart Citation
“…In patients harboring FSIP2 mutations, the defects in sperm are not limited to abnormalities in the FS but also cause abnormalities in the microtubule skeleton. A recent study has reported that FSIP2 mutant sperm show a globozoospermia phenotype in addition to flagella defects, and FSIP2 localizes in the acrosome and interacts with proteins associated with acrosome formation, indicating the potential function of FSIP2 in acrosome development (Zheng et al, 2022), which is consistent with single-cell RNA-seq data (Fang et al, 2021). FSIP2 has been demonstrated to interact with two other FS proteins, namely, AKAP3 and AKAP4, which are encoded by MMAF causative genes (Zhang G. et al, 2021;Liu Z. et al, 2022).…”
Section: Periaxonemal Structuressupporting
confidence: 84%
“…However, among the reported causative genes, few are directly related to FSs. FSIP2 , which encodes a FS-interacting protein, is involved in FS assembly, and FSIP2 defects have been reported to be related to MMAF ( Martinez et al, 2018 ; Liu Y. et al, 2019 ; Liu S. et al, 2021 ; Fang et al, 2021 ; Hou et al, 2022 ; Yuan et al, 2022 ; Zheng et al, 2022 ). In patients harboring FSIP2 mutations, the defects in sperm are not limited to abnormalities in the FS but also cause abnormalities in the microtubule skeleton.…”
Section: Pathogenic Genes and Their Function Inspermatogenesismentioning
confidence: 99%
“…To explore the role of ZMYND15 in regulating sperm morphology, we performed proteomic analysis on the testis of patient C and confirmed that ZMYND15 deficiency contributed to the downregulated expression of many spermatogenesis-related proteins. Importantly, the essential molecules for head elongation and acrosome formation, such as DPY19L2,23 SPACA119 and ZPBP,24 or for the biogenesis and assembly of flagella, such as FSIP2,25 AKAP4,26 ODF227 and DNAH2,28 were significantly downregulated in the patient compared with the normal control. In addition, Co-IP confirmed that ZMYND15 could interact with DPY19L2, FSIP2 and AKAP4, which further highlighted the significance of ZMYND15 in the spermiogenesis phase.…”
Section: Discussionmentioning
confidence: 90%
“…Previous mouse model data suggest that FSIP2 is only expressed in the testis [18,30], and the FSIP2 protein emerges in the testis of mice 21 days after birth and gradually accumulates until adulthood. Moreover, FSIP2 transcription begins in late spermatocyte developmental stage, and the gene is expressed in sperm cells and flagella at different spermatogenesis stages [18,20]. Further, immunofluorescence staining was performed using the sperm samples of patients with FSIP2 mutation and controls, which revealed that the FSIP2 antibody could not be observed in the piece of the sperm tail.…”
Section: Discussionmentioning
confidence: 99%